Risk Factors of Carcinoma Breast and their Changing Trends - Sabir, Farzana (International Journal of Pathology, 2022)
Introduction: Carcinoma breast (Ca Breast) is a multifactorial disease having various factors that contribute to its risk or occurrence. Objective: To investigate the frequency and changing trends of different known risk factors of Ca Breast. Materials and Methods Quantitative descriptive cross-sectional study was conducted at Abbas Institute of Medical Sciences (AIMS) Muzaffarabad, from July 2020 to June 2021. Seventy-five biopsy diagnosed patients of Ca breast in different stages of treatment presenting to Surgical OPD or admitted in wards in AIMS Hospital Muzaffarabad were included. The data was collected by using Questionnaire and was analyzed using SPSS version 25. Results: All patients were females 25-80 years of age. Out of these, 8 patients were in age group of 25-35 years, 35 in 36-55 while 32 in 56-80. 71 patients were married. Five cases were nulliparous. 6 patients had family history of Ca breast in first degree relatives. Females 29/32 in age group (56-80y) breastfed up to 2 years while remaining females only for< 6 months. BMI showed 12 obese, 26 overweight, 20 normal and 17 underweight females. Total number of children was 1-3 in17 females, 4-5 in 30 and 6 or more in19 females. Average age at menarche and menopause was 11 and 52 years respectively. Only 8 females used oral contraceptive pills. 42 females described low Physical activity, 33 moderate and none vigorous activity. Out of 15 working women, 5 were having history of night - shift work during whole period of job mostly related to medical profession. Conclusion: Risk of Ca breast is increasing in younger age group. Being married, Parity, exercise and breast feeding appears to be protective while obesity, overweight family history and night-shift work appear to be the contributing.